DESAIN SISTEM DATA LOGGER SUHU LINGKUNGAN BERBASIS ARDUINO NANO DAN SD CARD DENGAN DUKUNGAN RTC - Sururi Sururi; Muhamad Hilmansyah Susanta (LPPM Politeknik Pajajaran ICB Bandung, 2026)
This study aims to design and implement an environmental temperature and humidity data logger system based on Arduino Nano integrated with a DHT11 sensor, microSD storage module, and Real Time Clock (RTC). The system is designed to automatically and periodically record data, making it suitable as a simple and efficient environmental monitoring tool. The system operates by reading temperature and humidity data using the DHT11 sensor, which is then processed by the Arduino Nano and stored in a microSD card in CSV file format, complete with timestamp information provided by the RTC module. System testing was conducted with a data logging interval of 5 minutes to evaluate overall performance. The test results show that the system operates reliably and stably in continuously recording data without any data loss. The recorded temperature values range from 29.0°C to 29.9°C, while humidity values range from 68% to 69%. The stored data is well-structured and organized, making it easy for further analysis. Therefore, the developed data logger system can be used as an effective solution for automatic environmental temperature and humidity monitoring with good performance and scalability